2005
DOI: 10.1007/s00262-005-0011-z
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral-mediated transfer of human wild-type p53, GM-CSF and B7-1 genes results in growth suppression and autologous anti-tumor cytotoxicity of multiple myeloma cells in vitro

Abstract: Multiple myeloma (MM) remains incurable despite the use of high-dose chemotherapy and stem cell transplantation. However, immunotherapy is expected to offer long-term disease control, or even possibly a cure. We have previously demonstrated the suppressive effect of a recombinant adenovirus carrying human wild-type p53, granulocyte-macrophage colony-stimulating factor, and B7-1 genes (Ad-p53/GM-CSF/B7-1) on the growth of laryngeal cancer cells. In the present study, we evaluated the effects of an Ad-p53/GM-CSF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Thirty ÎŒg of each protein sample from cell lysate or serum‐free culture medium was loaded within an SDS‐PAGE gel followed by electrophoresis. Immunostaining was performed with PAEP (Invitrogen, South San Francisco, CA, USA), Phospho‐eIF2α (Cell signaling, Danvers, MA, USA) or α‐tubulin (Cell signaling) antibody followed by secondary antibody conjugated to horseradish peroxidase as described previously [19]. The blot was visualized with a Fujifilm Luminescent image analyser LAS‐3000 and analysed utilizing Multi‐Gauge V3.1 software (Fujifilm, Valhalla, NY, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Thirty ÎŒg of each protein sample from cell lysate or serum‐free culture medium was loaded within an SDS‐PAGE gel followed by electrophoresis. Immunostaining was performed with PAEP (Invitrogen, South San Francisco, CA, USA), Phospho‐eIF2α (Cell signaling, Danvers, MA, USA) or α‐tubulin (Cell signaling) antibody followed by secondary antibody conjugated to horseradish peroxidase as described previously [19]. The blot was visualized with a Fujifilm Luminescent image analyser LAS‐3000 and analysed utilizing Multi‐Gauge V3.1 software (Fujifilm, Valhalla, NY, USA).…”
Section: Methodsmentioning
confidence: 99%
“…16 Briefly, CNE-1 cells were infected with Ad-GFP, Adp53, Ad-p53/GM-CSF, Ad-p53/B7-1, or Adp53/GM-CSF/B7-1 at a MOI of 100 pfu/cell. Blank culture medium was used for mock infection.…”
Section: Cytotoxicity Assaymentioning
confidence: 99%
“…16,17 In this paper, we evaluated whether the recombinant adenovirus could induce tumor regression and subsequent antitumor response in vitro and in our NPC xenograft models of human immune system established huPBL nonobese diabetic/severe combined immunodeficiency (NOD/SCID) mice.…”
Section: Introductionmentioning
confidence: 99%
“…Although CTLs from human PBMC have been derived against a number of HLA-A2 binding peptides of p53, these CTL are less effective against p53 overexpressing tumor cells. Immunization with whole p53 protein delivered by viral vectors has the advantage of potential stimulation of responses targeting multiple MHC class I and II restricted epitopes (13, 42-43) . In the current study, the diverse nature of an immune response to p53 was confirmed by the demonstration of a higher percentage of IFN-Îł ICC positive cells in response to the p53 peptide library compared to both of the well known HLA-A2 epitopes combined (Figure 2(B)).…”
Section: Discussionmentioning
confidence: 99%